Introducing simulation based learning activities to physiotherapy course curricula - Dennis, D.; Sainsbury, David; Redwood, T.; Ng, Leo; Furness, A. (2016)
Background: Whilst relatively new in physiotherapy, simulation has been used in various medical and nursing programs to develop manual and communication skills and clinical reasoning. The primary aim of this study was to develop and introduce simulation activities into the physiotherapy curricula at an Australian University and evaluate students’ motivation to learn. The secondary aim was to evaluate differences in perceived value between first and second year students. Methods: During 2014, first and second year physiotherapy students at Curtin University, Western Australia enrolled in three units had the opportunity to participate in newly developed simulated scenarios as part of their program. On completion of these novel learning activities, students were invited to undertake the Instructional Materials Motivation Scale (IMMS) questionnaire. Results: Total IMMS scores for the three units (147, 137 and 156) indicated that overall, students found the simulation based learning activities motivating. First year students found that simulation gained their attention and was more enjoyable than second year students. Conclusions: As motivation entices people to learn and to complete activities, there may be great potential for improved learning outcomes using this modality in physiotherapy curricula, especially in the first year of the program.